The migration experience and multiple identities of Zimbabwean migrants in South Africa - Hungwe, Chipo (Online Research Journals, 2016)
This study shows how South African authorities and locals create 'spoilt identities' for non-South Africans through the makwerekwere image. It also shows how the non-South Africans, in this case Zimbabweans, try to resist such claims creating their own strategies and moral defences against such stereotyping. They also invent their own identity of South Africans. These Zimbabweans go on to reinvent themselves and create new identities as injiva. My argument is that while the process of identity formation is that of claims and counter-claims, it largely requires certain material, economic, symbolic resources to be deployed for successful identity formation. The command of certain resources and ability to adapt quickly to the new environment determines the level of success in evading the makwerekwere identity and also in carving a positive injiva identity.